2011
DOI: 10.1016/s0377-1237(11)60081-6
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of fracture resistance of interim fixed partial denture fabricated using polymethylmethacrylate and reinforced by different fibres for its optimal placement: an in vitro study

Abstract: INTRODUCTIONRehabilitation of partially edentulous patients using fixed partial denture (FPD) is a well-established treatment protocol since many decades. These FPDs require a laboratory phase of fabrication that varies from days to weeks. A dimensionally stable, strong, and accurate interim restoration is an important component of this treatment modality. These interim restorations provide pulpal protection, positional stability, occlusal function, strength, and aesthetics.Polymethylmethacrylate (PMMA) is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
(19 reference statements)
0
13
0
2
Order By: Relevance
“…Wetting with monomer facilitates the resin to contact surface of every fiber, ensuring better bonding resulting in higher fracture resistance. This premodification of the glass fiber supports the result that we have achieved and are in agreement with the studies done by Viswambaran et al .,[ 1 ] Gupta and Reddy[ 13 ] Naveen et al .,[ 14 ] and Kapri. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wetting with monomer facilitates the resin to contact surface of every fiber, ensuring better bonding resulting in higher fracture resistance. This premodification of the glass fiber supports the result that we have achieved and are in agreement with the studies done by Viswambaran et al .,[ 1 ] Gupta and Reddy[ 13 ] Naveen et al .,[ 14 ] and Kapri. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] It was also found that the strength of PMMA resin showed significant increase when reinforced with stainless steel wire, but results were found to be comparable with those of unidirectional glass fiber samples which coincides with the studies done by Viswambaran et al . [ 1 ] and Vallittu and Lassila[ 5 ] This can be attributed to possibility of adhesion of glass fiber with the resin matrix. In a similar study done by Geerts et al .,[ 18 ] stainless steel wire showed better results than glass fiber but was insignificant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transparency of this glassy material also helps in analyzing facture propagation during fracturing experiments (Alpern et al 2012). PMMA fracture behavior has been studied under different service applications (Viswambaran et al 2011), largely through experiments (Dalmas et al 2013) and continuum numerical analysis methods (Faye et al 2016). Micro-scale fracture propagation of these brittle materials has been examined, helping provide insight into the macroscopic mechanical properties (Rottler et al 2002).…”
mentioning
confidence: 99%